Human capital and industry 4.0: embracing technology and skills of accountants in the business organizations - Tey, Yii Pyin (2020)
Industry 4.0 and its rising technologies have been gaining tremendous popularity in recent years with the impacts and challenges that spark many interests in different aspects of the business environment. This revolution has brought about advanced development, innovation, transformation and variation to how production and manufacturing works, how employees play their roles and how decision makers made strategic decisions. One of the many affected roles is the accountant’s role. The accountant is an important person in the business where he or she keep tracks of the transaction and reports it accurately and reliably. However, with the rapid changes of technologies, many accountants and future accountants are concern about their relevance in their contribution to the business environment.